Does express delivery run ahead of stock price? - Chang, Jeffery (Jinfan); Yang, Shijie; Zhang, Bohui (Review of Finance, 2024)
We study the role of logistics information in the stock price discovery process. Using a proprietary dataset on parcel-level express delivery service records from one of the largest express service providers in China, we find that express delivery contains firm-specific information for stock pricing. A long/short portfolio of buying (selling) stocks with high (low) quarterly growth in the number of parcels sent by firms generates an 8.23 percent risk-adjusted annual return. The return predictability is more significantly driven by document, light, and business-to-business parcels, which reflects the intensity of a firm’s overall operations (rather than just sales growth), and by parcels sent to new addresses, which represents new business expansion. Echoing this return predictability, parcel growth also predicts firm growth, profitability, and earnings surprises. Finally, we provide evidence on return predictability associated with topology of logistic network identified by parcel delivery data.